Management of the Psycho-Pedagogical Work on Prevention of Antisocial Behavior of Troubled Teenagers - Stukalenko, Nina M.; Zhantemirova, Madina B.; Abibulayeva, AizhanÐ° B.; Ermekova, Zhadyra K.; Beisenbayev, Sadybek K. (International Review of Management and Marketing, 2016)
In the theory and practice of education management great emphasis is made on organization of educational work with troubled teenagers, conducted by school psychologists. Analysis of the antisocial behavior of troubled teenagers has shown that the number of children, which are characterized by school and social maladjustment and persistent violations of conduct, increases each year. Searching for ways to improve the effectiveness of teachers' and psychologists' efforts, when working with troubled teenagers at school and outside of school, is one of the major problems of education management. Present research is focused on study of the features of this pressing issue. The article summarizes the results of the conducted study on improving the effectiveness of correctional work with screwed-up kids. The obtained outcomes are of theoretical and practical significance, and can be applied in education management to prevent anti-social behavior of troubled children. It can be useful for both practicing teachers and psychologists. Keywords: Education management, teachers' and psychologists' operation management, antisocial behavior, deviant behavior, JEL Classifications: I210, I280, Z180